Preparation method of reinforced resin for high-temperature-resistant lubricating oil glass fiber filter material
By using epoxy-modified polyurethane aqueous emulsion and vinyl silicone oil in lubricating oil glass fiber filter materials to form a multi-crosslinked structure, the problem of performance degradation of existing reinforced resins at high temperatures is solved, and excellent tensile strength and oil resistance can be maintained at a high temperature of 200°C.
Patent Information
- Application Number
- CN202510965574.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-09-12
AI Technical Summary
The performance of the reinforcing resin of existing lubricating oil glass fiber filter materials deteriorates at high temperatures and cannot meet the application requirements of high temperature resistance. In addition, the bonding strength is low, which easily causes the glass fiber to fall off.
Epoxy-modified polyurethane aqueous emulsion is compounded with vinyl silicone oil, crosslinking agent, cosolvent and composite emulsifier to form a three-dimensional network structure through multiple crosslinking, thereby improving the high temperature resistance and bonding strength of the resin.
It can maintain excellent tensile strength and oil resistance at high temperatures of 200°C, improve the durability and processing performance of glass fiber filter materials, and meet the application requirements of lubricating oil glass fiber filter materials.
Smart Images

Figure CN120623433A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical fields of polymer synthesis technology and filter materials, and particularly relates to a method for preparing a reinforced resin for high-temperature resistant lubricating oil glass fiber filter material. Background Art
[0002] Lubricating oil plays the role of lubrication, cooling, cleaning, sealing, rust prevention, power transmission, vibration reduction and noise reduction in the engine lubrication system of mechanical equipment such as aircraft and ships, thereby ensuring the efficient and stable operation of the equipment and extending its service life. It is known as the "blood" of mechanical equipment. High-temperature lubricating oil filter media need to cope with extreme temperatures (≥200°C), chemical corrosion and dynamic filtration challenges. The material must be resistant to high-temperature aging, have high filtration accuracy (≥99% interception of 5μm particles) and chemical stability, while balancing pressure drop and dust holding capacity. Its core application scenarios include harsh environments such as engines and turbines.
[0003] Glass fiber media can operate stably and long-term at temperatures between 200 and 300°C, effectively intercepting tiny particles (≥99% filtration efficiency). It exhibits high-temperature resistance, chemical stability, high mechanical strength, and low pressure drop. Its advantages include long life, resistance to oil oxidation, and low energy consumption. Therefore, glass fiber filter material is the primary material for lubricating oil filtration media. However, the low surface hydroxyl content of glass fiber results in poor bonding strength and a loose structure in the resulting glass fiber base paper. In practical engineering applications, the glass fiber base paper is typically reinforced with resin. Only after this reaction can the resulting glass fiber filter material meet application requirements. Optimizing the fiber shedding prevention process and regularly monitoring the pressure differential and oil contamination status are required to ensure long-term reliability. Traditional reinforcing resins for lubricating oil glass fiber filter media are mostly thermoplastic or thermosetting acrylic resins. Thermoplastic acrylic resins have a low degree of crosslinking, resulting in a decrease in strength after the resin swells and softens in oil at high temperatures, making them unable to meet the high-temperature resistance requirements of applications.
[0004] Patent US2015174509A1 reports a filter medium in which a layer of glass fiber is impregnated with 5% thermoplastic acrylic resin. However, the filter material has a large flow pore size and serves only as a pre-filtration layer. Furthermore, the resin bonding strength is low, and the glass fiber easily falls off into the oil, exacerbating contamination.
[0005] Patent CN110066359B provides a water-soluble thermosetting acrylic resin that can impart excellent tensile strength, elongation at break, and oil and high-temperature resistance to glass fiber filter media. However, this system has a high curing temperature and is susceptible to aging at temperatures exceeding 150°C, resulting in reduced strength and pulse resistance.
[0006] Patent CN116874722A discloses a silicone / polyurethane / epoxy composite resin emulsion. When applied to glass fiber filter media, this emulsion imparts excellent tensile strength and retention, resulting in enhanced oil and high-temperature resistance. However, this system, a simple compound of silicone / polyurethane / epoxy resins, fails to maximize the performance of all three. Furthermore, the physical compounding process, without further chemical crosslinking, is not conducive to application in sustained high-temperature environments.
[0007] With the changes in the application scope and working environment of the lubricating oil system, higher requirements are placed on the high-temperature oil resistance and bonding performance of the bonded resin. The currently disclosed filter material products or reinforced resins cannot meet the requirements of practical application processing and durability. Therefore, there is an urgent need to find a lubricating oil that can withstand higher temperatures and at the same time improve the processing performance of the enhanced filter material and a durable and environmentally friendly reinforced resin system. Summary of the Invention
[0008] The object of the present invention is to provide a method for preparing a reinforced resin for high-temperature resistant lubricating oil glass fiber filter material, so as to solve the technical problems in the prior art.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] The present invention provides a method for preparing a reinforced resin for a high-temperature resistant lubricating oil glass fiber filter material, comprising the following steps:
[0011] Step (1) adding dehydrated epoxy polyester polyol and catalyst to a reaction kettle, adding isocyanate after heating, slowly adding a hydrophilic chain extender and adding a solvent to adjust the viscosity after the reaction, continuing the reaction, adding hydroxy acrylate, continuing to heat, keeping the temperature, cooling, adding TEA for neutralization, and then adding deionized water for high-speed dispersion, discharging, and removing impurities to obtain an epoxy-modified polyurethane aqueous emulsion;
[0012] In the above process, epoxy-modified polyurethane is prepared by reacting epoxy polyester polyol with isocyanate, passing through a hydrophilic chain extender, and then end-capping with hydroxy acrylic acid.
[0013] Step (2) dispersing epoxy-modified polyurethane aqueous emulsion, vinyl silicone oil, crosslinking agent, cosolvent, water, and composite emulsifier at high speed to obtain a mixed emulsion, taking 1 / 3 and adding it into a kettle, adding 1 / 3 of the initiator dropwise, heating, reacting, and continuously adding the remaining 2 / 3 of the mixed emulsion and the remaining 2 / 3 of the initiator dropwise within 2.5-3.5 hours, heating, keeping the temperature, cooling and discharging, adding a water-based epoxy resin curing agent, and obtaining a reinforcing resin for high-temperature resistant lubricating oil glass fiber filter material.
[0014] Preferably, in step (1), the solvent is acetone; and the epoxy polyester polyol is selected from commercially available products: 8015 (Wanhua Chemical), EPP-200 (Shandong Dongda Chemical), C2200 (Covestro), E-300 (Huntsman).
[0015] Preferably, in step (1), the heating temperature is 65-75°C; the reaction time is 2-4h; the continued reaction time is 1-3h; the continued heating temperature is 75-85°C; the insulation time is 2-4h; the cooling temperature is 40-45°C; the neutralization time is 0.5-1.5h; the high-speed dispersion time is 0.5-1.5h; and the impurity removal method is to remove the residual solvent by rotary evaporation.
[0016] Preferably, in step (1), the isocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.
[0017] Preferably, in step (1), the hydrophilic chain extender includes at least one of dimethylol propionic acid and dimethylol butyric acid.
[0018] Preferably, in step (1), the hydroxyacrylate includes at least one of 2-hydroxyethyl methacrylate and 2-hydroxyethyl acrylate; and the catalyst is organic bismuth.
[0019] Preferably, in step (1), the epoxy-modified polyurethane accounts for 50-80% by mass of the reaction monomers.
[0020] More preferably, in step (1), the epoxy-modified polyurethane accounts for 60-70% by mass of the reaction monomers.
[0021] Preferably, in step (2), the vinyl silicone oil refers to a vinyl functionalized polydimethylsiloxane having a structural formula as shown in formula (III) or formula (IV):
[0022] (CH3)3SiO[(CH3)2SiO]m[(CH2=CH)(CH3)SiO]nSi(CH3)3(III)
[0023] The structure of formula (III) is: methyl vinyl polysiloxane with a vinyl group in the middle of the molecular chain.
[0024] (CH2=CH)Si(CH3)2O[(CH3)2SiO] n (CH3)2Si(CH=CH2)(IV)
[0025] The structure of formula (IV) is: polydimethylsiloxane with a vinyl group at each end of the molecular chain;
[0026] In formula (III) and formula (IV), m is 1-4000, n is 1-4000, and the molecular weight of (III) and (IV) is between 300-300000.
[0027] Preferably, in step (2), the molecular weight of the vinyl silicone oil is 500-5000; and the mass ratio of the vinyl silicone oil to the reaction monomers is 10-35%.
[0028] More preferably, in step (2), the vinyl silicone oil accounts for 20-30% by mass of the reaction monomers.
[0029] Preferably, in step (2), the cross-linking agent comprises at least one of N-methoxyacrylamide, methylenebisacrylamide, and diacetoneacrylamide; and the cross-linking agent accounts for 5-10% by mass of the reaction monomers.
[0030] Preferably, in step (2), the cosolvent includes at least one of tripropylene glycol, tripropylene glycol monomethyl ether, dipropylene glycol, and dipropylene glycol monomethyl ether.
[0031] Preferably, in step (2), the composite emulsifier includes at least one of sodium dodecylbenzenesulfonate (SDS), alkylphenol polyoxyethylene ether (OP), and polyethylene oxide sorbitan monostearate (Tween).
[0032] Preferably, in step (2), the water-soluble initiator is ammonium persulfate or potassium persulfate KPS.
[0033] Preferably, in step (2), the initiator is a mixture of 0.2g KPS and 10g water; the water-based epoxy resin curing agent is WannerH123; the heating temperature is 70-80°C; the reaction method is: at a rotation speed of 100-200r / min, the reaction is 15-20min; the heating temperature is 80-90°C; and the holding time is 0.5-1.5h.
[0034] The reinforced resin for high-temperature resistant lubricating oil glass fiber filter material is prepared by the method for preparing the reinforced resin for high-temperature resistant lubricating oil glass fiber filter material.
[0035] The present invention also provides a method for applying the above-mentioned reinforcing resin for high-temperature resistant lubricating oil glass fiber filter material to lubricating oil glass fiber filter material, comprising the following steps:
[0036] The high temperature resistant lubricating oil glass fiber filter material is diluted with reinforcing resin by adding water to obtain reinforcing resin impregnation, and then impregnated, coated or sprayed on glass fiber base paper, and dried at 145-155°C to obtain lubricating oil glass fiber filter material.
[0037] Preferably, the amount of the reinforcing resin impregnation liquid is 4-6%.
[0038] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0039] 1. The present invention introduces organic silicon structural segments with better high-temperature resistance into the secondary polymerization of epoxy-modified polyurethane to further enhance the high-temperature resistance. Simultaneously, an amide-type high-temperature crosslinking agent is introduced into the polymerization reaction, thereby forming a triple crosslink of epoxy, amide, and siloxy bonds, forming a three-dimensional crosslinked structure, thereby enhancing the cohesive force between the entire resin molecules and forming multiple crosslinks during the coating curing process. The increased crosslinking density of the coating enhances the impact resistance of the coating, thereby resolving the various performance issues of the glass fiber paper under persistent high-temperature conditions and improving its durability. The treated glass fiber paper can be stably stored for a long time, thus facilitating industrial continuous production.
[0040] 2. After the reinforced resin emulsion prepared by the present invention is applied to the impregnation of glass fiber filter material, it not only gives the filter material excellent tensile strength, meeting the pleating requirements of the reinforced filter material processing, but also the reinforced filter material has excellent oil resistance and high temperature resistance, which can meet the working conditions application requirements of 200°C high-temperature lubricating oil, and at the same time can effectively improve the durability of glass fiber paper.
[0041] 3. After the reinforced resin emulsion prepared by the present invention is applied to the impregnation of glass fiber filter material, it not only gives the filter material excellent tensile strength, meeting the pleating requirements of the reinforced filter material processing, but also the reinforced filter material has excellent oil resistance and high temperature resistance, which can meet the working conditions application requirements of 200°C high-temperature lubricating oil, and at the same time can effectively improve the durability of glass fiber paper. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0043] Figure 1 This is an infrared spectrum of Example 1 of the reinforced resin for high-temperature resistant lubricating oil glass fiber filter material of the present invention;
[0044] Figure 2 It is a schematic diagram of the synthesis of the particle size distribution of the reinforced resin emulsion prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0046] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.
[0047] Examples 1-4
[0048] Examples 1-4 disclose a reinforced resin for high-temperature resistant lubricating oil glass fiber filter material. The raw material composition is shown in Table 1 and is prepared by a method comprising the following steps:
[0049] Step (1) Synthesis of epoxy-modified polyurethane:
[0050] Add dehydrated epoxy polyester polyol and catalyst to a reactor, heat to 65-75°C, add isocyanate and stir evenly, react for 2-4 hours, slowly dropwise add hydrophilic chain extender DMPA and add solvent to adjust viscosity, continue to react for 1-3 hours, add hydroxy acrylate, heat to 75-85°C, keep warm for 2-4 hours, cool to 40-45°C after end-capping, add TEA to neutralize for 0.5-1.5 hours, then add deionized water and disperse at high speed for 0.5-1.5 hours, discharge, and remove residual solvent by rotary evaporation to obtain an epoxy-modified polyurethane aqueous emulsion with a solid content of 50%;
[0051] Step (2) Synthesis of Enhanced Resin:
[0052] After the synthesized epoxy-modified polyurethane aqueous emulsion, vinyl silicone oil, crosslinking agent, cosolvent, water, and composite emulsifier are dispersed at high speed, 1 / 3 of the mixed emulsion is added to a bottle, 1 / 3 of the initiator is added dropwise, and the mixture is heated to 70-80°C. The rotation speed of the electric stirrer is set to 100-200 r / min. After the system reacts for about 15-20 minutes, a blue phenomenon will appear; the remaining mixed emulsion and the remaining initiator are added dropwise separately, and the dripping is controlled to be completed continuously within 2.5-3.5 hours. After the dripping is completed, the system is heated to 80-90°C, kept warm for 0.5-1.5 hours, and finally cooled and discharged to obtain a white emulsion with a slightly light blue light and a solid content of 40%. A measured amount of water-based curing agent Wanner H123 is added for compounding to form a reinforced resin emulsion.
[0053] The reinforcing resin emulsion is compounded according to the theoretical value that the epoxy equivalent is equal to the active hydrogen equivalent.
[0054] The initiator is a mixture of 0.2 g KPS and 10 g water.
[0055] The reinforced resin for high temperature resistant lubricating oil glass fiber filter material can be obtained by completing the above steps. The results are shown in Table 1.
[0056] Table 1 Composition of Reinforced Resin Raw Materials in Examples 1-4
[0057] Table 1
[0058]
[0059]
[0060] As shown in Table 1, Examples 1-4 can form stable and blue-light emulsions within the scope of the present invention. C 2200 (Covestro), E-300 (Huntsman), by replacing isocyanate with diphenylmethane diisocyanate and hexamethylene diisocyanate, replacing the cosolvent with dipropylene glycol and dipropylene glycol monomethyl ether, and replacing the initiator with ammonium persulfate, can also obtain a reinforcing resin for high-temperature resistant lubricating oil glass fiber filter material that meets the above requirements.
[0061] Figure 1 : The infrared spectrum of Example 1 shows: 3100-3600cm -1 NH, 1700cm -1 The strong peak near it is C=O. This is the characteristic peak of polyurethane and amide. 1250cm -1 At the peak, and 800cm -1 Nearby is the characteristic absorption peak of epoxy. 1000-1100cm -1 The interval corresponds to the Si-O-Si asymmetric stretching vibration peak.
[0062] Comparative Examples 1-3
[0063] Comparative Examples 1-3 prepared a reinforced resin for high-temperature resistant lubricating oil glass fiber filter material. The raw material composition is shown in Table 2. The preparation was carried out according to the same steps and methods as in Examples 1-4. The results are shown in Table 2:
[0064] Table 2: Comparative Example Raw Material Composition
[0065]
[0066]
[0067] Examples 5-8
[0068] Examples 5-8 and Comparative Examples 4-6 respectively prepared high-temperature resistant lubricating oil glass fiber filter materials using the reinforced resins for high-temperature resistant lubricating oil glass fiber filter materials of Examples 1-4 and Comparative Examples 1-3.
[0069] Mix 3g of the reinforced resin emulsion prepared in Examples 1-4 or Comparative Examples 1-3 with 98g of water and stir until uniform. Lay the formed micro-glass fiber paper flat and immerse it in the diluent for 30 seconds. Remove it, remove it, and cure it at 150°C for 15 minutes to obtain a high-temperature lubricating oil-resistant glass fiber filter material. Maintain a sizing agent at 4-6%.
[0070] Test Case
[0071] The performance of Examples 1-8 and Comparative Examples 1-6 was tested using the following method:
[0072] 1. Emulsion particle size test
[0073] The particle size of the reinforced resins prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention was tested by using a Mastersizer 2000 laser particle size analyzer (Malvern, UK) to test the size and distribution of the latex particles. The test results are as follows: Figure 2 shown.
[0074] 2. Stiffness test
[0075] The stiffness test was performed in accordance with GB / T 22364-2018. The stiffness of the glass fiber filter materials of Examples 5-8 and Comparative Examples 4-6 was tested using a bending stiffness tester. The sample length was 70 mm, the bending length was 50 mm, and the bending angle was 15°.
[0076] 3. Tensile strength
[0077] The tensile strength test was performed in accordance with GB / T 12914-2023. The tensile strength and tensile strength retention of the glass fiber filter materials of Examples 5-8 and Comparative Examples 4-6 were tested using a tensile strength meter. The sample length was 100 mm and the width was 15 mm.
[0078] 4. High temperature resistant oil performance test
[0079] The glass fiber filter materials prepared in Examples 5-8 and Comparative Examples 4-6 were immersed in aviation lubricating oil at an oil temperature of 200°C for 48 hours so that both sides could be fully exposed to the oil. After being taken out, the surface lubricating oil was gently wiped off with oil-absorbing paper, and the filter materials were then washed three times with petroleum ether to wash off the residual lubricating oil. Finally, they were placed in an oven at 150°C and dried to constant weight before the stiffness test.
[0080] 5. Durability-Failure Test
[0081] Failure testing is measured using test time and the sample's stiffness retention rate. In a failure test, the sample is first tested for stiffness after preparation, designated X0. The sample is then placed in a storage environment at 85±2°C and 85±2% relative humidity. The stiffness is measured multiple times at regular intervals, designated X1, X2, X3, and so on, at regular intervals. The stiffness retention rate is calculated as the ratio of the test stiffness values (X1, X2, X3, and so on, Xn) to the initial stiffness value (X0). A stiffness retention rate of less than 80% is considered failure. Failure testing can reflect the durability of filter materials.
[0082] The glass fiber filter papers prepared in Examples 5-8 and Comparative Examples 4-6 were tested for pleating performance. The test results are shown in Figure 3 and Table 4 below:
[0083] Table 3: Performance data of glass fiber filter papers prepared in Examples 5-8 and Comparative Examples 4-6
[0084]
[0085] As shown in Table 3, the initial tensile strength, stiffness and durability of ordinary polyester polyols are all decreased compared with Example 5. This is because there is no curing agent, which affects its cross-linking. Compared with Example 5, the amide cross-linking agent is less during the secondary synthesis, and the initial tensile strength and stiffness are all decreased, and the durability decreases significantly. After 500h, the stiffness retention rate is halved. This shows that the introduction of the amide cross-linking agent can improve the cohesion between the entire resin molecules and improve durability. Compared with Example 5, the amount of siloxane used is reduced, the initial tensile strength decreases, and the stiffness increases, indicating that the epoxy resin accounts for too high a proportion, making the cured film too hard and brittle, resulting in poor tensile strength and a decrease in durability.
[0086] Table 4: High temperature oil resistance performance data of glass fiber filter paper treated with reinforced resin emulsion
[0087]
[0088] As can be seen from the results in Table 4, compared with Example 5, the tensile strength retention rate of ordinary polyester polyol after 200°C high-temperature oil is only 41.82%, and the stiffness retention rate is 46.88%. Epoxy polyester plays a very important role in high temperature resistance. Compared with Example 5, the amide cross-linking agent is less during the secondary synthesis. After 200°C high-temperature oil, the tensile strength retention rate is only 67.11%, and the stiffness retention rate is 59.46%. This shows that the introduction of the amide cross-linking agent can form multiple cross-links with epoxy and siloxy bonds during the coating curing process, thereby increasing the cross-linking density of the coating and enhancing the high-temperature resistance of the coating. Compared with Example 5, the amount of siloxane used is reduced. After 200°C high-temperature oil, the tensile strength retention rate and stiffness retention rate are about 50%, indicating that the proportion of epoxy resin is too high, making the cured film too hard and brittle, and the adhesion is poor.
[0089] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
[0090] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a reinforced resin for high temperature resistant lubricating oil glass fiber filter material, characterized in that: The following steps are involved: Step (1) adding dehydrated epoxy polyester polyol and catalyst to a reaction kettle, adding isocyanate after heating, slowly adding a hydrophilic chain extender and adding a solvent to adjust the viscosity after the reaction, continuing the reaction, adding hydroxy acrylate, continuing to heat, keeping the temperature, cooling, adding TEA for neutralization, and then adding deionized water for high-speed dispersion, discharging, and removing impurities to obtain an epoxy-modified polyurethane aqueous emulsion; Step (2) dispersing epoxy modified polyurethane aqueous emulsion, vinyl silicone oil, crosslinking agent, cosolvent, water and composite emulsifier at high speed to obtain a mixed emulsion, taking 1 / 3 and adding it into a kettle, adding 1 / 3 of initiator dropwise, heating and reacting, adding the remaining 2 / 3 of the mixed emulsion and the remaining 2 / 3 of the initiator dropwise within 2.5-3.5 hours, heating, keeping the temperature, cooling and discharging, adding water-based epoxy resin curing agent, and obtaining a reinforcing resin for high temperature resistant lubricating oil glass fiber filter material.
2. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (1), the solvent is acetone; the heating temperature is 65-75°C; the reaction time is 2-4 hours; the continued reaction time is 1-3 hours; the continued heating temperature is 75-85°C; the heat preservation time is 2-4 hours; the cooling temperature is 40-45°C; the neutralization time is 0.5-1.5 hours; the high-speed dispersion time is 0.5-1.5 hours; and the impurity removal method is to remove the residual solvent by rotary evaporation.
3. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (1), the isocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate; and the hydrophilic chain extender includes at least one of dimethylol propionic acid and dimethylol butyric acid.
4. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (1), the hydroxy acrylate includes at least one of 2-hydroxyethyl methacrylate and 2-hydroxyethyl acrylate; the catalyst is organic bismuth; and the epoxy-modified polyurethane accounts for 50-80% by mass of the reaction monomers.
5. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In step (2), the vinyl silicone oil refers to a vinyl functionalized polydimethylsiloxane having a structural formula as shown in formula (III) or formula (IV): (CH3)3SiO[(CH3)2SiO]m[(CH2=CH)(CH3)SiO]nSi(CH3)3 (III) The structure of formula (III) is: methyl vinyl polysiloxane with a vinyl group in the middle of the molecular chain; <h2 style=";text-align:left;direction:ltr">(CH2=CH)Si(CH3)2O[(CH3)2SiO]<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> (CH3)2Si(CH=CH2)(IV) The structure of formula (IV) is: polydimethylsiloxane with a vinyl group at each end of the molecular chain; In formula (III) and formula (IV), m is 1-4000, n is 1-4000, and the molecular weight of (III) and (IV) is between 300-300000.
6. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (2), the molecular weight of the vinyl silicone oil is 500-5000; the vinyl silicone oil accounts for 10-35% of the mass ratio of the reaction monomer; the cross-linking agent includes at least one of N-methoxyacrylamide, methylenebisacrylamide, and diacetone acrylamide; and the cross-linking agent accounts for 5-10% of the mass ratio of the reaction monomer.
7. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (2), the co-solvent includes at least one of tripropylene glycol, tripropylene glycol monomethyl ether, dipropylene glycol, and dipropylene glycol monomethyl ether.
8. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (2), the composite emulsifier includes at least one of sodium dodecylbenzene sulfonate (SDS), alkylphenol polyoxyethylene ether (OP), and polyethylene oxide sorbitan monostearate (Tween).
9. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (2), the water-soluble initiator is ammonium persulfate or potassium persulfate (KPS).
10. The reinforced resin for high temperature resistant lubricating oil glass fiber filter material according to claim 1, characterized in that: In the step (2), the water-based epoxy resin curing agent is Wanner H123; the heating temperature is 70-80°C; the reaction method is: at a rotation speed of 100-200 r / min, the reaction is 15-20 minutes; the heating temperature is 80-90°C; and the insulation time is 0.5-1.5 hours.
Citation Information
Patent Citations
A water-soluble thermosetting acrylic resin, its preparation method and application
CN110066359B
Filter media with fine staple fibers
US20150174509A1